The Relationship Between Physical Activity And Resilience Levels In College Students - Adh Dhiya' Husnaputri; Tri Laksono; Agus Riyanto (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Students enrolled at universities are recognized for their ability to carry out tasks independently, demonstrating a more mature and developed mindset.. Student lecture activities involve physical activity which can affect physical activity patterns and resilience levels. Resilience among students is viewed as highly significant because it plays a crucial role in shaping their thinking patterns and contributes to their success in tackling challenges. Objective: To investigate how physical activity impacts resilience in university students. Methods: In this study, descriptive quantitative methods with a cross-sectional design were utilized. A purposive sampling method was applied, and it included a total of 611 respondents. Physical activity was measured using the International Physical Activity Questionnaire-Short Form (IPAQ-SF), while resilience levels were assessed using the Connor Davidson Resilience Scale-25 (CD-RISC-25). The data were analyzed through univariate analysis, normality tests, and bivariate analysis using the Spearman Rank test. Results: A significant positive relationship between physical activity and resilience (r = 0.212, p = 0.000) was revealed by the correlation analysis. Additionally, a significant relationship between heavy physical activity and resilience (r = 0.211, p = 0.023) was also identified. Conclusion: A significant positive relationship has been identified between physical activity and resilience, including intense physical activity.